Peningkatan Pertumbuhan Ekonomi Melalui Pendirian Baitul Tamwil Muhammadiyah (BTM) Bagi Masyarakat Pasar Rumput Jakarta Selatan - Fitriyanto, Arif Fitriyanto; Rianto, Adi (SYUKUR (Jurnal Inovasi Sosial dan Pengabdian Masyarakat), 2018)
Desire to engage in enterpreneurial activity often faltred because of limitations capital and the absence of a business entity that lends funds to them at no interest cost (usury) except for loan sharks which actually discourages them to entrepreneurship. This situation made us moved to help people who want to open a business but have limited capital or business funds and help the local community there to provide assistance or business training to minimize the losses that will arise later by establishing Baitul Tanwil Muhammadiyah (BTM) which is certainly based on sharia and not apply the usury system. This paper aims to describe the activities of community service programs undertaken in order to improve the economic growth of the people of Pasar Rumput South Jakarta.